Hacia una re-construcción de la sociabilidad ilustrada: las Sociedades gaditanas de Amigos del País - Franco Rubio, Gloria A. (Cuadernos de Historia Moderna, 2002)
This arride tries to show a new vision to the studies about the sociability in the age of the Enlightenment through one of the most emblematie institutions: te Sociedades Económicas de Amigos del País, studying the which emerged in the province of Cádiz in the last third of the eigtheenth century